PENGAMANAN CONTROL AKSES PADA SISTEM PENDUKUNG KEPUTUSAN PENERIMA BANTUAN SOSIAL MENGGUNAKAN RBAC DAN SAW - Febi Wulan Adha Febi Wulan Adha; Kasmawi (LPPM Universitas Abdurrab, 2026)
The distribution of social assistance at the village level still faces various challenges, such as subjective beneficiary selection processes, lack of transparency, and weak control over system user access rights. These conditions may lead to inaccurate targeting, reduce public trust in social assistance programs, and create opportunities for data manipulation and misuse. This study aims to design and develop a decision support system for the Autonomous BPNT social assistance program in Buruk Bakul Village by implementing Role-Based Access Control (RBAC) and the Simple Additive Weighting (SAW) method. RBAC is applied to regulate user access rights based on roles, namely Village Administrator, Social Assistance Operator, and RT/RW, ensuring that each user can only access features according to their authority. The SAW method is utilized to support the objective assessment of prospective beneficiaries based on three main criteria: low-income households not receiving other assistance, DTKS status, and possession of the Bengkalis Prosperous Card. The evaluation is conducted using criterion weights that have been previously determined by the village authorities. The results indicate that the implementation of RBAC improves data security and the orderly management of social assistance information, while the SAW method produces an objective and measurable ranking process based on predefined criteria and weights. The developed system is expected to enhance targeting accuracy, transparency, and accountability in the distribution of social assistance at the village level.